Radar systems, peak detection and tracking - Kolawole, Michael O. (Oxford ; Boston : Newnes, 2002)
As well as being fully up-to-date, this book provides wider subject coverage than many other radar books. The inclusion of a chapter on Skywave Radar, and full consideration of HF / OTH issues makes this book especially relevant for communications engineers and the defence sector. * Explains key theory and mathematics from square one, using case studies where relevant * Designed so that mathematical sections can be skipped with no loss of continuity by those needing only a qualitative understanding * Theoretical content, presented alongside applications, and working examples, make the book suitable to students or others new to the subject as well as a professional reference.
Preface. PART I: Essential Relational Functions; Understanding Radar Fundamentals; Antenna Physics and Radar Measurements; The Radar Equations; Antenna Arrays. PART II IONOSPHERE AND HF SKYWAVE RADAR: The Ionosphere and Its Effect on HF Skywave Propagation; Skywave radar. PART III PROBABILITY THEORY, DECISION THEORY AND SIGNAL PEAK DETECTION: Elements of probability theory and statistical concepts; Decision theory; Signal Peak Detection. PART IV: Parameter Estimation and Filtering; Tracking. Conclusion; Summary; References; Problems; Glossary of Terms; Index.
Includes bibliographical references (p. [348]-354) and index.
Keywords: Radar; Electronic books